Update breast cancer 2024 part 3 - patients with advanced stage breast cancer = Update Mammakarzinom 2024 Teil 3 : Patientinnen mit fortgeschrittenen Stadien des Mammakarzinoms - Lüftner, Diana; Kolberg, Hans-Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter Andreas; Jackisch, Christian; Marmé, Frederik; Keller, Katharina; Hörner, Manuel; et al. (Geburtshilfe und Frauenheilkunde, 2025)
The use of CDK4/6 inhibitors, the new PI3K/AKT-kinase inhibitors, selective estrogen receptor-degraders (SERDs), antibody-drug conjugates, immune therapies and PARP inhibitors in recent years has resulted in a marked change in the therapy landscape for patients with advanced stage breast cancer. CDK4/6 inhibitors, trastuzumab deruxtecan, and sacituzumab govitecan have all been shown to provide significant overall survival benefits compared to conventional chemotherapy. Other substances are also showing promising results and hold out the hope that further analysis of the overall survival benefits will be available in the near future. The speed at which studies are now being carried out has markedly increased, and conferences and specialist journals are now constant sources of new information. This review summarizes the most recent publications and conference presentations on the treatment of patients with advanced stage breast cancer.
Online veröffentlicht: 15. Mai 2025
Gesehen am 28.08.2025